DETERMINATION OF TECHNICAL PARAMETERS OF LIGHTWEIGHT FIRE-RESISTANT SHEMATO GISHT (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
A number of works are being carried out to improve the quality, variety, and mechanical and other properties of refractory products. In particular, obtaining lightweight types of refractory products is one of the areas that is being widely studied in the current industry. The use of various wood chips and coal powders to give light weight to kaolin-based raw materials is among the works being carried out in this area. A number of experiments have been carried out by adding additives in different proportions and results have been obtained.